2020
DOI: 10.3389/fonc.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Contrast-Enhancement for Monitoring of PRRT 177Lu-DOTATATE in Pancreatic Neuroendocrine Tumor Patients

Abstract: Conclusions: Early changes in contrast-enhancement and arterial attenuation in PNET liver metastases may for CECT monitoring of PRRT yield complementary information to evaluation by RECIST 1.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…After completion of PRRT, the tumor vascularization decreased in the majority of P-NET lesions, as reflected by their CT contrast-enhancement. A corresponding reduction in P-NEN vascularization between the CT at baseline and on follow-up CT post-PRRT has previously been reported by Pettersson et al [20]. Thus, although the total administered activity (GBq) was similar in P-NEN and SI-NEN patients, the decline in absorbed doses (Gy) in the tumors over consecutive PRRT cycles was significant in the majority of P-NEN patients, as shown in Figures 3 and 4.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…After completion of PRRT, the tumor vascularization decreased in the majority of P-NET lesions, as reflected by their CT contrast-enhancement. A corresponding reduction in P-NEN vascularization between the CT at baseline and on follow-up CT post-PRRT has previously been reported by Pettersson et al [20]. Thus, although the total administered activity (GBq) was similar in P-NEN and SI-NEN patients, the decline in absorbed doses (Gy) in the tumors over consecutive PRRT cycles was significant in the majority of P-NEN patients, as shown in Figures 3 and 4.…”
Section: Discussionsupporting
confidence: 79%
“…The vascularity of primary pancreatic tumors and P-NENs has earlier been analyzed and was found to correlate to tumor classification and survival [ 18 , 19 ]. Also, fold changes of contrast-enhancement in P-NEN metastases has been shown to correlate to PRRT outcome [ 20 ]. These findings are in agreement with preclinical studies on vascularization in radiated tumors in mice [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Change in arterial tumor attenuation and contrast enhancement is another criterion, which was recently evaluated by Pettersson et al [ 87 ] in a retrospective cohort of 52 patients with metastatic pNETs who underwent ceCT at baseline, mid-treatment and at 3 months follow-up. Their study showed a significant decrease of the maximum arterial attenuation of liver metastases between baseline (217 ± 62 HU) and follow-up (198 ± 62 HU; p = 0.025).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were screened for inclusion using a previously described cohort of PanNET patients (n=151) undergoing PRRT with 177 Lu-DOTATATE (21). Inclusion criteria were at least one hypervascular liver metastasis at baseline on contrast-enhanced computed tomography (CECT) of adequate technical quality.…”
Section: Patients and Imagingmentioning
confidence: 99%